Qualidade e conservação pós-colheita de frutos de seis cultivares de coqueiro Anão - Santos Filha, Maria Elizabete Carvalho dos (Universidade Federal Rural do Semi-Árido, 2007)
In the objective to compare the potentiality of yellow and red cultivars in relation to Green Dwarf cultivar explored in Jiqui commercially, the present work was divided in two experiments, where the first experiment had as objective to evaluate the quality of the water of six Dwarf coconut cultivars (Green of Jiqui - AveJ, Yellow of Gramame - AAG, Yellowda- Malaysia - AAM, Red of Gramame - AVG, Red-da-Malaysia - AVM, Vermelho-dos- Camarões - AVC), and in the second experiment was evaluated the potential of conservation of these fruits under refrigeration and modified atmosphere. Also, the fruits were submitted to the storage (12±1°C and 90±2% UR), in which had been evaluated in intervals of 0, 7, 14, 26, 40 and 50 days of storage after the harvest, observing its physical and sensorial behavior of the coconut water. The fruits were harvested to the seven months after the fertilization, in the Embrapa Half-North, Parnaíba-PI, and carried out to the Laboratory of Postharvest of the Embrapa, Fortaleza-CE. In the first experiment, in the field two plants of each cultivar had been chosen at chance and two fruits had been taken per plant, where these fruits had been evaluated soon after the harvest, and in the laboratory the experiment was carried out in an entirely randomized design with six treatments (cultivars) and four replications. The physical characterizations (length, diameter, weight, volume of the water, relation water/fruit and color of the rind) of these fruits had been carried through individually and after that the physicalchemical of the coconut water (Solid Soluble Totals SST, Total and Reducing Soluble Sugars, Total Acidity Titulável - ATT, SST/ATT, pH and turbidness, beyond the analysis of minerals and sensorial attributes of the coconut water. ESTAT was the statistical package used for analysis of variance of the data. In the second experiment, an entirelyrandomized design was used, in a 6 x 6 factorial scheme, with six cultivars evaluated in six times (0, 7, 14, 26, 40 and 50 days after the harvest), with four replications. The fruits of the six cultivars of dwarfed coconut palm, were individually involved with film PVC of 15μ and stored in cooled chamber. Physical-chemical evaluations were made as those it was carried through in the previous experiment, beyond the external appearance and color of the rind. The analysis of variance of the data was made through Sisvar Package. The water quality of the and red coconut cultivars was similar to that one of Green cultivar, indicating that these had the same presented potential for consumption in natura and/or the industrialization, whose these red cultivars, mainly AVC and AVG, had presented good acceptance for the provers of its water of coconut, presenting good performance until the 50 days of storage. Thus, It is admitted that the yellow and red cultivars consist of in a new viable alternative to export these fruits to the markets most distant
Quality and conservation postharvest of fruits of six cultivars of dwarf coconut palm
Keywords: Conservation; Quality; Coconut water in natura; Cultivars; Conservação; Qualidade; Água-de-coco in natura; Cultivares; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA